THE EFFECTS OF BOKO HARAM ACTIVITIES ON TOURISM BUSINESSES IN NORTH EASTERN NIGERIA - Inyang, Oduduabasi; Samuel Arokoyu (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study was carried out to measure terrorism effects on components of tourism businesses (hotels) in northeastern Nigeria using Boko Haram as a case study. Secondary data on nature, date, and the number of fatalities from the Boko Haram attack was sourced from the Armed Conflict Location & Event Data (ACLED). Data on tourism businesses including hotel room occupancy rate, revenue profile, and employees’ profile was sourced from each state tourism development board. A total of 558 hotels were selected in a one-stage cluster sampling technique. The study adopts a longitudinal research design where inferential statistics was performed with the use of SPSS. Results revealed that Boko Haram attacks had significant effects on tourism businesses contributing to the decline in the number of hotel employees, revenue, and room occupancy rate of hotels in the region. The study, therefore, recommends intense media promotion of the areas and States not majorly affected by the crisis, rebuilding of areas and States recovered from the group, provisions of more resilient security apparatus, and general development of social, educational, and economic infrastructures to help revamp the socioeconomic life of the area.